Exosomes Regulate Interclonal Communication on Osteogenic Differentiation Among Heterogeneous Osteogenic Single-Cell Clones Through PINK1/Parkin-Mediated Mitophagy - Fei, Dongdong; Xia, Yanmin; Zhai, Qiming; Wang, Yazheng; Zhou, Feng; Zhao, Wanmin; He, Xiaoning; Wang, Qintao; Jin, Yan; Li, Bei (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stem cells (MSCs) are intrinsically heterogeneous and are comprised of distinct subpopulations that differ in their differentiation potential. A deeper understanding of the heterogeneity and intercellular communication within these heterogeneous subpopulations has significant implications for the potential of MSC-based therapy from the bench to the clinic. Here, we focused on the clonal osteogenic heterogeneity of periodontal ligament stem cells (PDLSCs) and explored how interclonal communication affects osteogenic differentiation among these heterogeneous single-cell colonies (SCCs), and sought to determine the underlying mechanisms. Alkaline phosphatase (ALP) and Alizarin red staining identified the presence of SCCs with high (H-SCCs) and low osteogenic ability (L-SCCs). Conditioned medium derived from H-SCCs (H-CM) promoted mineralized nodule formation to a greater extent than that derived from L-SCCs (L-CM), which served as target cells (TCs). However, treatment with the exosome biogenesis/release inhibitor GW4869 reduced the H-CM- and L-CM-related osteogenic differentiation-promoting potential. We further found that exosomes secreted by H-SCCs (H-Exo) were superior to those secreted by L-SCCs (L-Exo) in promoting the osteogenic differentiation of TCs. Mechanistically, TCs stimulated with H-CM and H-Exo exhibited higher levels of PINK1/Parkin-mediated mitophagy, while gain- and loss-of-function experiments showed that PINK1/Parkin-mediated mitophagy was positively associated with SCC osteogenic differentiation. Furthermore, PINK1 knock-down in H-Exo- and L-Exo-stimulated TCs inhibited their osteogenic differentiation through inhibiting PINK1/Parkin-mediated mitophagy. Our study uncovers a previously unrecognized mechanism that exosome-mediated PINK1/Parkin-dependent mitophagy regulates interclonal communication among SCCs with osteogenic heterogeneity.